Evolution of Food Prices and its Impact on Food Security in Algeria - Halmouche, Cheikh; Madi, Mohamed Brahim (جامعة ابن خلدون تيارت - الملحقة الجامعية قصر الشلالة, 2023)
This study aims to present the food security situation in Algeria through the World Food Security Index and identify the challenges that prevent the achievement of the goal of food security in Algeria. This study found concluded that the state of food security in Algeria is still in the process of development, and in order to enhance and support food security, a framework for appropriate policies must be put in place to maintain food security.
Keywords: أسعار الغذاء -- الأمن الغذائي -- الجزائر